2016
DOI: 10.1158/1078-0432.ccr-15-1265
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Label, Randomized Phase II Trial of Personalized Peptide Vaccination in Patients with Bladder Cancer that Progressed after Platinum-Based Chemotherapy

Abstract: Purpose: The prognosis of platinum-based chemotherapyresistant metastatic urothelial cancer of the bladder remains poor. Personalized selection of the right peptides for each patient could be a novel approach for a cancer vaccine to boost anticancer immunity.Experimental Design: In this randomized, open-label, phase II study, patients ages !18 years with progressive bladder cancer after first-line platinum-based chemotherapy were randomly assigned (1:1) to receive personalized peptide vaccination (PPV) plus be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(107 citation statements)
references
References 22 publications
(27 reference statements)
2
105
0
Order By: Relevance
“…Treatment was fairly well tolerated; almost all AEs were of grade 1 or 2; there were no grade 4 AEs or treatment-related deaths. Obviously, as the authors concluded, further large-scale, randomized trials are needed to confirm these results [52]. …”
Section: Other Immunotherapiesmentioning
confidence: 99%
“…Treatment was fairly well tolerated; almost all AEs were of grade 1 or 2; there were no grade 4 AEs or treatment-related deaths. Obviously, as the authors concluded, further large-scale, randomized trials are needed to confirm these results [52]. …”
Section: Other Immunotherapiesmentioning
confidence: 99%
“…We have used one of the HLA-A24-restricted epitopes, EGFR 800-809 , as a candidate peptide for personalized peptide vaccination, in which vaccine antigens are selected and administered based on the pre-existing host immunity before vaccination (Sasada et al, 2014). Recent clinical trials of personalized peptide vaccination have demonstrated significantly prolonged overall survival in patients with advanced cancers, including prostate and bladder cancer, through induction of antigen-specific T cells (Sasada et al, 2014; Noguchi et al, 2016; Yoshimura et al, 2016). …”
Section: Cellular Immune Responses To Wild Type Egfrmentioning
confidence: 99%
“…For muscle invasive disease, treatment with a personalized vaccine was recently showed to improve overall survival versus best supportive care [32]. In this study, patients were randomized to best supportive care with or without a personalized vaccine that included 2–4 of 31 candidate peptides selected based on HLA types and peptide-reactive IgG titers.…”
Section: Therapeutic Targeting Of Dysfunctional Anti-tumor Immunitymentioning
confidence: 99%